2012
DOI: 10.1016/j.brainres.2012.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in white matter development during adolescence: A DTI study

Abstract: Adolescence is a complex transitional period in human development, composing physical maturation, cognitive and social behavioral changes. The objective of this study is to investigate sex differences in white matter development and the associations between intelligence and white matter microstructure in the adolescent brain using diffusion tensor imaging (DTI) and tract-based spatial statistics (TBSS). In a cohort of 16 typically-developing adolescents aged 13 to 17 years, longitudinal DTI data were recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
87
6
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 66 publications
15
87
6
2
Order By: Relevance
“…Our findings that QA may affect the relationship between age and FA, specifically in males, is also noteworthy. Young males typically show a larger association between FA and age (Wang et al, 2012), a finding we corroborate. This sex difference is thought to reflect earlier white matter maturation in females than in males.…”
Section: 0 Discussionsupporting
confidence: 84%
“…Our findings that QA may affect the relationship between age and FA, specifically in males, is also noteworthy. Young males typically show a larger association between FA and age (Wang et al, 2012), a finding we corroborate. This sex difference is thought to reflect earlier white matter maturation in females than in males.…”
Section: 0 Discussionsupporting
confidence: 84%
“…Despite a growing literature of differential white matter effects between boys and girls, the current study was unable to statistically demonstrate such an interaction in associations between white matter integrity and cognition. Previous work has shown sex differences, both in brain development and in behavioral and cognitive associations (Hanggi et al, 2010;Schmithorst, 2009;Schmithorst et al, 2008;Simmonds et al, 2014;Wang et al, 2012). One potential explanation for the lack of an interaction effect in the present study is that the effects are focal rather than global.…”
Section: Discussioncontrasting
confidence: 71%
“…Further studies looking at changes of FA in these tracts following intervention might help us in understanding the effect of different types of reading therapies on neuroplasticity in AF and ILF and the influence of the integrity of these tracts, particularly in the right hemisphere, on reading ability. Note that the relatively small number of participants precluded separating males and females in the analysis, although we know that sex influences white matter developmental trajectories in general (Wang et al, 2012). Future studies should consider the differences between genders as well as testing our hypotheses about the role of the right hemisphere by enrolling a clinical population as well.…”
Section: Discussionmentioning
confidence: 99%
“…Tract-Based Spatial Statistics (TBSS) (Smith et al, 2006) was then used to prepare the individual diffusion maps for voxel-based group analysis by performing the following steps (see Figure 4): all subject FA images were aligned to a template of averaged FA images (FMRIB-58) in Montreal Neurological Institute (MNI) space using a non-linear registration algorithm implemented in FNIRT (FMRIB's Non-linear Registration Tool) (Rueckert et al, 1998). We have previously found that the MNI adult framework is adequate for co-registration of DTI data from adolescent brains (Wilke, Schmithorst, & Holland, 2003; Wang et al, 2012 ). After transformation into MNI space, a cohort mean FA image was created and thinned to generate a cohort mean FA skeleton of the white matter tracts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation